In Situ Metal Deposition on Perhydropolysilazane-Derived Silica for Structural Color Surfaces with Antiviral Activity - Burak, Darya; RAHMAN MD ABDUR; Seo, Dong-Chan; Byun, Ji Young; HAN, JOON SOO; Lee, Seung Eun; Cho, So-Hye (American Chemical Society, 2023)
Structural coloration has recently sparked considerable attention on the laboratory and industrial scale. Structural colors can create vivid, saturated, and long-lasting colors on metallic surfaces for optical filters, digital displays, and surface decoration. This study used an all-solution, low-cost method, free of a specific setup procedure, to fabricate structural colors of a multilayered metal-dielectric structure based on interference effects within a Fabry？Perot cavity. The insulating (dielectric) layer was produced from perhydropolysilazane, an inorganic silicon-containing polymer, from which hydrogen was liberated during conversion into silica and applied in situ to reduce metallic nanoparticles on the silica surface. This simple manufacturing technique contributes to the fabrication of large, high-quality surfaces, which could potentially be employed for surface decoration. The fabricated surfaces also exhibited excellent hydrophobic properties with contact angles up to 137°, endowing them with self-cleaning properties. In addition, the antiviral and antibacterial impact of the silver (Ag)/silica (SiO2)/stainless steel (SUS) film was also examined, as Ag has been reported to have antimicrobial and, recently, antiviral properties. According to three independently conducted antiviral assays, the fluorescence expression of virus-infected cells, PCR analysis, and modified tissue culture infectious dose assay, the film inhibited lentivirus by 75, 97, and 99% when exposed to the virus for 20 min, 1 h, and 20 min, respectively. Furthermore, the film had exceptional antibacterial activity with no colony growth observed for 24 and 12 h of inoculation. It is thus conceivable that these structural color-based films can be used to not only decorate metal surfaces with aesthetic colors but also limit virus and bacterium propagation successfully.